Discriminative analyses of various upper body tests in professional Rugby-League players - Baker, D. G.; Newton, R. U. (International Journal of Sports Physiology and Performance, 2006)
To examine the upper body strength, speed, power, and strength-endurance of rugby-league players of different ranks. These data could provide information pertinent to the importance of these factors for different grades of rugby league and for positional groups in those different grades. Methods: Sixty rugby-league players, 20 participants each in the elite, national first-division league (NRL), state-based second-division league (SRL), and intracity third-division league (CRL), served as subjects. Maximal upper body strength, power, speed, and muscle endurance were assessed using the bench-press exercise. Results: The NRL players were significantly stronger (141.4 ± 15.4 kg) than SRL (126.6 ± 13.1 kg, ES = 1.033) and CRL (108.1 kg ± 11.6, ES = 2.458) and more powerful (NRL = 680 ± 99 W) than SRL (591 ± 72 W, ES = 1.037) and CRL players (521 ± 71 W, ES = 1.867). The differences in speed (NRL = 345 ± 31 W, SRL = 319 ± 29 W, CRL = 303 ± 29 W; ES = 0.884 and 1.409, respectively) and strength-endurance (NRL = 36 ± 7 reps, SRL = 32 reps ± 7, CRL = 24 ± 5 reps; ES = 0.521 and 1.984, respectively) were not as pronounced. Conclusions: Of the tests undertaken, maximal strength best describes players who attain NRL ranking. Maximum power and strength-endurance were also strong descriptors of attainment of NRL level. Upper body speed appears less likely to strongly discriminate between players who attain NRL level and those who do not. These results tended to hold true across the different team positional groupings.